Free Flap Scalp Reconstruction in a 91-Year-Old Patient under Local-Regional Anesthesia: Case Report and Review of the Literature - Carey, Joseph Nicholas; Watt, Andrew J.; Ho, Oscar; Zeidler, Kamakshi; Lee, Gordon Kwanlyp (Journal of Reconstructive Microsurgery, 2012)
In the elderly population with significant medical comorbidities, the safety of general anesthesia is often in question. In the head and neck, where regional and extradural anesthesia are not options, reconstruction of defects requiring free tissue transfer becomes a particular challenge for patients in whom general anesthesia is contraindicated. We present a case of a scalp reconstruction utilizing a latissimus dorsi free flap in a 91-year-old man performed entirely under local and regional anesthesia. General anesthesia was contraindicated secondary to the patient's multiple medical comorbidities. A paravertebral block was used for the harvest of the latissimus dorsi muscle and skin grafts. The microvascular portion of the procedure and the inset were performed under local anesthesia alone. The patient tolerated the procedure, and the operation was successful. This case is unique in that there are no published reports of head and neck free tissue transfer being performed entirely under local-regional anesthesia. We conclude that despite the medical challenges of performing complex reconstruction in elderly patients, expedient free tissue transfer can offer patients access to successful reconstruction.
Keywords: scalp reconstruction; local anesthesia; latissimus dorsi; paravertebral block